Обряди та ритуальні дійства у старцівському середовищі - Кушпет, В. (Народна творчість та етнографія, 2007)
The investigator of old men unions gives typology of rituals which existed in the midst of old men, in particular he analyses salutatory and prayerful rituals, mystic rituals and rituals of initiation. The author also gives rich library material from archive of Institute of Art Studies, Folkloristics and Ethnology (IAFE).